2013
DOI: 10.1097/iae.0b013e3182852446
|View full text |Cite
|
Sign up to set email alerts
|

Polypoidal Choroidal Vasculopathy

Abstract: Practical guidance on the clinical management of PCV is proposed based on expert evaluation of current evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 238 publications
(150 citation statements)
references
References 167 publications
(226 reference statements)
2
146
0
2
Order By: Relevance
“…The ICG angiogram is an important tool for studying the choroidal vasculature and is considered the gold standard test for PCV diagnosis [12,30]. It is likely that not performing systematic ICG angiograms in patients with neovascular AMD results in an underdiagnosis of PCV cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ICG angiogram is an important tool for studying the choroidal vasculature and is considered the gold standard test for PCV diagnosis [12,30]. It is likely that not performing systematic ICG angiograms in patients with neovascular AMD results in an underdiagnosis of PCV cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a greater number of PCV cases would be diagnosed worldwide, if an ICG angiogram was performed at least in suspicious cases. Koh et al [12] emphasized that an ICG angiogram should be performed for the diagnosis of PCV when routine ophthalmoscopic examination indicates a serosanguineous maculopathy with one of the following features: (1) clinically visible orange-red subretinal nodules, (2) spontaneous massive subretinal hemorrhage, (3) notched or hemorrhagic PED and (4) a lack of response to anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an initial treatment plan for submacular hemorrhage with a presumable diagnosis of AMD might not be appropriate in Asian patients. In PCV patients, PDT with or without anti-VEGF has been reported to be more effective than anti-VEGF monotherapy in some studies [30,31,32,33]. Papavasileiou et al [26] reported favorable treatment outcomes when they differentially treated submacular hemorrhage based on underlying causes; after t-PA and C 3 F 8 gas injection, ranibizumab was administered in patients with typical AMD, and PDT was applied for PCV within 2 weeks of the initial injection [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, Song et al [141] reported that IVR without PDT for PCV in Korean patients resulted in significant visual and anatomical improvements over a 1-year follow-up period, and other reports suggested that the disappearance of the polypoidal lesions occurred at a high rate in PCV cases after anti-VEGF monotherapy [74,142,143]. A recent review suggested an overall improvement of the VA of PCV patients using IVR [144], and a most recent multicenter randomized controlled trial (LAPTOP study) revealed that IVR monotherapy achieved a significantly better visual prognosis than PDT monotherapy in PCV patients [145]. However, Matsumiya et al [16,17] reported that the degree of improvement in the VA in PCV patients was lower than that of tAMD patients treated by anti-VEGF monotherapy.…”
Section: Response To Treatmentmentioning
confidence: 99%